2003
DOI: 10.1046/j.0963-7214.2003.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Pets a Healthy Pleasure? The Influence of Pets on Blood Pressure

Abstract: 2000). Thermal hyperalgesia and mechanical allodynia produced by intrathecal administration of the Human Immunodeficiency Virus-1 (HIV-1) envelope glycoprotein, gp120. Brain Research, 861 ,[105][106][107][108][109][110][111][112][113][114][115][116]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 13 publications
3
94
1
5
Order By: Relevance
“…A positive or beneficial relationship between pet ownership and autonomic function or cardiovascular reactivity to stress has been reported in most 13,[57][58][59][60][61][62][63][64][65][66][67][68][69] but not all [69][70][71][72] published studies. For example, cardiovascular reactivity to stress (ie, mental arithmetic and cold pressor) was assessed in 240 couples, half of whom owned a cat or dog.…”
Section: Pet Ownership and Autonomic Function And Cardiovascular Reacmentioning
confidence: 99%
“…A positive or beneficial relationship between pet ownership and autonomic function or cardiovascular reactivity to stress has been reported in most 13,[57][58][59][60][61][62][63][64][65][66][67][68][69] but not all [69][70][71][72] published studies. For example, cardiovascular reactivity to stress (ie, mental arithmetic and cold pressor) was assessed in 240 couples, half of whom owned a cat or dog.…”
Section: Pet Ownership and Autonomic Function And Cardiovascular Reacmentioning
confidence: 99%
“…Moreover, the average scores for students in the lecture (60%), reading (55%), and control (52%) conditions were not significantly different from one another. Saville et al also discussed several limitations to their study, including the fact that multiple-choice quizzes may not be best for identifying differences in learning and that the article they used (Allen, 2003) contained information on a topic (i.e., the relation between pet ownership and health) about which students may have been knowledgeable before participating in the study (hence, one possible reason why students in the control condition scored above chance on the quiz). nevertheless, because students in the interteaching condition performed significantly better than students in the lecture and readings conditions-who performed no better than students in a control condition after just 1 week-Saville et al concluded that interteaching might be an effective alternative to other teaching methods.…”
Section: Is Interteaching Effective?mentioning
confidence: 99%
“…Saville, Zinn, and Elliott (2005) conducted the first systematic investigation of interteaching, a lab-based study that compared interteaching to more traditional teaching methods. They randomly assigned students to one of four conditions-interteaching, lecture, reading, or control-and exposed students in the first three conditions to material from an article on pet ownership and health (Allen, 2003). Students then returned to the lab 1 week later and took a 10-item, multiple-choice quiz.…”
Section: Is Interteaching Effective?mentioning
confidence: 99%
“…HAI can reduce blood pressure (Allen, 2003) and frequency of doctor visits (Headey, 1999), and is associated with increased life expectancy (Allen, Shykoff, & Izzo, 2001;Friedmann, Thomas, Wilson, & Turner, 1995).…”
Section: Benefits Of Petsmentioning
confidence: 99%